2021
DOI: 10.1021/acsami.1c09379
|View full text |Cite
|
Sign up to set email alerts
|

Active Targeting Significantly Outperforms Nanoparticle Size in Facilitating Tumor-Specific Uptake in Orthotopic Pancreatic Cancer

Abstract: Nanoparticles are widely studied as theranostic vehicles for cancer; however, clinical translation has been limited due to poor tumor specificity. Features that maximize tumor uptake remain controversial, particularly when using clinically relevant models. We report a systematic study that assesses two major features for the impact on tumor specificity, i.e., active vs passive targeting and nanoparticle size, to evaluate relative influences in vivo. Active targeting via the V7 peptide is superior to passive ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 94 publications
0
24
0
Order By: Relevance
“…A recent study confirmed the importance of tumor-targeting surface modifications [84]. Utilizing V7 peptide-conjugated MSNs in an orthotopic PDAC model, MacCuaig and colleagues showed that active targeting of MSNs (i.e., including surface modifications to increase tumor cell uptake) outperforms passive targeting (i.e., no tumor targeting modifications on the MSNs) irrespective of nanoparticle size [84]. However, it is important to note that improved uptake and cytotoxicity in vitro does not always translate to similar findings in vivo, as PEGylated MSNs showed higher tumor uptake compared to PEG-transferrin-modified MSNs in one study [47].…”
Section: Cytotoxicity Of Classical Msns In Pdacmentioning
confidence: 77%
See 4 more Smart Citations
“…A recent study confirmed the importance of tumor-targeting surface modifications [84]. Utilizing V7 peptide-conjugated MSNs in an orthotopic PDAC model, MacCuaig and colleagues showed that active targeting of MSNs (i.e., including surface modifications to increase tumor cell uptake) outperforms passive targeting (i.e., no tumor targeting modifications on the MSNs) irrespective of nanoparticle size [84]. However, it is important to note that improved uptake and cytotoxicity in vitro does not always translate to similar findings in vivo, as PEGylated MSNs showed higher tumor uptake compared to PEG-transferrin-modified MSNs in one study [47].…”
Section: Cytotoxicity Of Classical Msns In Pdacmentioning
confidence: 77%
“…Pioneering studies showed that surface modification by conjugation with polyethyleneimine (PEI) [37], folic acid [82], or monoclonal antibodies targeting anti-claudin4 and anti-mesothelin [83] indeed improved nanoparticle uptake by PDAC cells, whereas modification with polyethylene glycol (PEG) was shown to enhance biodistribution and circulation time in experimental animal models [40,42]. More recent studies use alternative surface modifications to target chemotherapeutics to PDAC tumors, and MSNs have been conjugated with transferrin [46,47,83], urokinase plasminogen activator [54], anti-GPC1, anti-tMUC1 [48], or V7 [84] peptides for this purpose. As envisioned, cellular uptake was increased using tumortargeting moieties compared to controls lacking a modification both in vitro [46,47,83] and in vivo [48,54,84].…”
Section: Cytotoxicity Of Classical Msns In Pdacmentioning
confidence: 99%
See 3 more Smart Citations